2020
DOI: 10.1111/1365-2435.13601
|View full text |Cite
|
Sign up to set email alerts
|

Food web properties vary with climate and land use in South African streams

Abstract: 1. Land use intensification and climate change are two prominent drivers of variation in biological communities. However, we know very little about how these two potential environmental stressors interact. Here we use a stable isotope approach to quantify how animal communities respond to urban and agriculture land use, and to latitudinal variation in climate (rainfall and temperature), in 29 streams across South Africa.2. Community structure was shaped by both land use and climatic factors. The taxonomic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 74 publications
(98 reference statements)
1
37
0
Order By: Relevance
“…A1). Longterm monitoring could reveal negative or positive responses to global warming, depending on precipitation patterns and species' thermal tolerances (Dallas and Rivers-Moore, 2014;Paukert et al, 2017;Jackson et al, 2020;Kao et al, 2020). Although dam surface area is likely to be important in practice, e.g., due to variation in total fish population size, dam area was not included in any models and is likely unimportant when selecting dams for a longterm monitoring programme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A1). Longterm monitoring could reveal negative or positive responses to global warming, depending on precipitation patterns and species' thermal tolerances (Dallas and Rivers-Moore, 2014;Paukert et al, 2017;Jackson et al, 2020;Kao et al, 2020). Although dam surface area is likely to be important in practice, e.g., due to variation in total fish population size, dam area was not included in any models and is likely unimportant when selecting dams for a longterm monitoring programme.…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed groups of dams with shared climatic characteristics that seem to associate with certain primary catchments due to the strong effect of the escarpment (Figs 1 and 2A). Although the gillnet models cannot generalise CPUE estimates to unsampled dams, these climate clusters roughly indicate dams where certain fish species could thrive, or dams where fish populations should be monitored for vulnerability to climate change (Britz et al, 2015;Jackson et al, 2020;Kao et al, 2020). Dominant species' CPUE estimates broadly match the climate clusters, with comparatively higher CPUE for L. aeneus and L. capensis associated with the relatively cooler Cluster 1, whereas O. mossambicus are largely present in Cluster 4 where maximum temperature is higher (Table 2, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of warming and predation were considered additive if models excluding their interaction term had lower AIC values. For the nonadditive interactions, interaction effect sizes (F-values) were subtracted from the sum of the main effect sizes producing values representing the difference between additive and interactive effects, following previous studies (Jackson et al 2020; Lakeman-Fraser and Ewers 2014). If the value was positive, then the relationship was considered to be antagonistic (the effect of the drivers were reduced when acting interactively); if however, the value was negative, then the relationship was considered to be synergistic (the effect of the drivers were increased when acting interactively) (Table S1).…”
Section: Analysesmentioning
confidence: 99%